1997
DOI: 10.1007/bf02385812
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of colon cancer followed by polymyositis: Report of a case and review of the literature

Abstract: The direct causal relationship between dermatomyositis-polymyositis (PM) and malignancy remains controversial. We describe herein the case of a patient who underwent surgical treatment for colon cancer, which had preceded the onset of PM with tumor relapse. The PM markedly improved following the initiation of steroid therapy, and has remained under control, probably as a result of chemotherapy. The current concepts of variable clinical courses and the possible mechanism for the association of PM with malignanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Various population-based studies have shown association of colorectal cancer with DM [5,6]. However, its association with PM is limited to few case reports [8][9][10][11]. The diagnosis of cancer can be before, after or simultaneously with myositis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Various population-based studies have shown association of colorectal cancer with DM [5,6]. However, its association with PM is limited to few case reports [8][9][10][11]. The diagnosis of cancer can be before, after or simultaneously with myositis [6].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However its association with PM is limited to few case reports. 8,9,10,11 The diagnosis of cancer can be before, after or simultaneously with myositis. 6 Studies have shown that the peak incidence of cancer detection is within the rst year of diagnosis of myositis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that the PM in the present case was directly related to colon cancer. Case reports of PM associated with colon cancer are very rare [6]. Although Nyui et al [6] reported PM associated with colon cancer, the myositis in their case markedly improved with steroid therapy.…”
Section: Discussionmentioning
confidence: 99%